Use of pesticide by the vegetables farmers and occupational health hazards posed by pesticide application in Mymensingh district (Research in Agriculture Livestock and Fisheries, 2020)
In Bangladesh, the use of different types of pesticides has increased in crop protection purposes. These pesticides may affect farmers’ health and contaminate the aquatic environment. The objectives of the current study were to assess the use of pesticide by the vegetable farmers and their associated health hazards caused by pesticide application. A structured questionnaire was used to collect data from fifty vegetable farmers of three different villages at Mymensingh Sadar Upazila during February and March of 2019. Results showed that the mostly used pesticide was Mefonexam (used by 40% interviewed farmers), followed by Thiamethoxam + Chlorantraniliprole (24%), Profenofos + Cypermethrin (20%), and Propineb (10%). The highest application frequency was reported as 30 times for Ebamectin. The present study recorded Chlorpyrifos as the highest using dose (7.5 kg/ha) in vegetable farms. Approximately 42% of the farmers were reported to increase the amount of applying pesticide in the last 5 years where 46% continued same. More than half of the respondents (56%) were reported to use at least one protective measure during pesticide application. Most of the interviewed farmers (56%) reported no health risk while applying pesticides. Sixty percent of the interviewed farmers were claimed to have faced some negative health symptoms. Respondents were reported to face headache (31%), eye irritation (27%), vomiting (20%), dizziness (12%), and skin irritation (7%). The study indicates that the farmers of Mymensingh are not conscious about the proper use of pesticide, thus this kind of injudicious use of pesticide causes serious occupational health hazards.Res. Agric., Livest. Fish.7(1): 165-174, April 2020